2019
DOI: 10.56093/ijas.v89i11.95309
|View full text |Cite
|
Sign up to set email alerts
|

System productivity enhancement in coconut (Cocos nucifera) garden by intercropping with flower crops in Assam

Abstract: The field experiment was conducted at Horticultural Research Station, Kahikuchi of Assam Agricultural University for four consecutive years (2012–13 to 2015–16) to study the performance of flower crops as intercrop in adult coconut (Cocos nucifera) garden spaced at 7.5 m × 7.5 m taking five commercial flower crops, viz. Tuberose (Polianthes tuberosa) var. Single, Gerbera (Gerbera jamesonii) var. Red Monarch, Bird of Paradise (Strelitzia reginae) var. Glauca, Gladiolus (Gladiolus grandiflorus) var. Oscar, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(4 reference statements)
1
1
0
Order By: Relevance
“…This balanced approach provides a sustainable and profitable model for farmers looking to maximize their returns from intercropping systems. The outcomes [26] of the research support the evidence that intercropping can increase the primary crop's production of nuts. The coordinated use of resources increases overall efficiency, leading to increased coconut crop yields [27].…”
Section: Economics Of Coconut-based Intercropping Systemssupporting
confidence: 62%
“…This balanced approach provides a sustainable and profitable model for farmers looking to maximize their returns from intercropping systems. The outcomes [26] of the research support the evidence that intercropping can increase the primary crop's production of nuts. The coordinated use of resources increases overall efficiency, leading to increased coconut crop yields [27].…”
Section: Economics Of Coconut-based Intercropping Systemssupporting
confidence: 62%
“…Basavaraju et al (2011) [1] also reported increased economic returns in the intercropping systems of coconut with medicinal and aromatic plants. It is well accepted that inter cropping system under coconut is more profitable than mono cropping which promises to the farmers a lot besides generating additional employment opportunity (Nath, 2002) [3] .…”
Section: Resultsmentioning
confidence: 99%